Ewing's Sarcoma and Primary Osseous Lymphoma: Spectrum of Imaging Appearances - Weber, Marc-André; Papakonstantinou, Olympia; Nikodinovska, Violeta Vasilevska; Vanhoenacker, Filip M. (Seminars in Musculoskeletal Radiology, 2019)
Ewing's sarcoma (ES) is a rare, highly malignant anaplastic stem cell tumor. Histologically, the tumor consists of uniform densely packed small monomorphic cells with round nuclei. The typical appearance at hematoxylin and eosin (H&E) staining is small blue round cells without any matrix formation. On conventional radiography, ES typically presents as a permeative lesion in the diaphysis of a long bone in a child. A large soft tissue component is another characteristic feature, best depicted by magnetic resonance imaging.Primary osseous lymphomas are most commonly highly malignant B-cell lymphomas. At H&E histologic staining, the tumor stroma consists of diffuse round-cell infiltrates that resembles the appearance of ES. Although there is no typical imaging appearance of an osseous lymphoma, it should be considered in an adult presenting with a Lodwick grade II or III lesion in the metaphysis or diaphysis of a large long bone, the pelvis, or the vertebral column. Histologic confirmation is mandatory.
Keywords: Ewing's Sarcoma; primary osseous lymphoma; radiography; magnetic resonance imaging; review